RANCANG BANGUN APLIKASI PENGARSIPAN SURAT DAN DISPOSISI PADA DINAS PERHUBUNGAN KOTA MADIUN BERBASIS WEBSITE - Eka Yopa Sarda Yopa (LPPM Universitas Merdeka Madiun, 2025)
Mail management is important for an agency. In the secretariat section at the Madiun City Transportation Service Office. The management of letters contained in these agencies in the form of incoming and outgoing letters still uses the method of recording in a register book or ledger, so far the process of managing letters is done manually which takes quite a long time when searching for letters when needed, and storage in a safe rack can be cause the quality of physical documents is not guaranteed. For this reason, a laravel website-based archiving application was created in this study. The system development method used in this study is the waterfall analysis method which consists of four stages, namely the requirements and old system stages, the new system design stage, the implementation and testing stages. Making this website using the laravel framework and MySQL database. The results of this study are an application for filing letters and dispositions (APSD). The application was tested using the blackbox method, and was said to be successful. Based on this, the application in this study is expected to facilitate the filing of incoming and outgoing letters and the process of distributing letters runs easily.